Rủi ro từ Deepfakes và hành vi tự bảo vệ cá nhân - Nguyễn Thu, Thủy; Đinh Minh, Trang; Phan Thị Thanh, Hoa (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
The purpose of this study is to examine the impact of perceived Deepfakes-related risks on internet users’ self-protection behavior. This study examines how three dimensions of perceived Deepfakes-related risk, including (1) information manipulation risk, (2) privacy risk, and (3) security risk, influence online users’ self-protection behaviors. This study also applies the Theory of Reasoned Action to investigate the mediating role of attitudes toward self-protection behavior in these relationships. The study surveys 289 internet users from Vietnam. The results indicate that perceived Deepfakes-related security and privacy risks have both direct and indirect effects on self-protection behaviors, with attitudes toward self-protection behavior acting as a mediator. Information manipulation risk influences self-protection behaviors but does not affect attitudes toward self-protection behavior. The findings provide valuable insights for policymakers, technology developers, and users on enhancing security awareness and promoting effective self-protection measures in online transactions.